When in Rome... On Local Norms and Sentencing Decisions. Issue 2 (9th September 2021) - Abrams, David; Galbiati, Roberto; Henry, Emeric; Philippe, Arnaud
Abstract: We study spatial variation in criminal sentencing. We show the existence of local sentencing practices varying widely even across geographically proximate areas. Using compulsory rotation of judges in North Carolina, we find that judges arriving in a new court gradually converge toward local sentencing practices. We provide evidence that convergence in sentencing corresponds to a process of learning about local practices, which is accelerated by the presence of senior judges in the district, and that these sentencing practices are correlated with local norms of behavior. Finally, we discuss the theoretical implications of these results for the optimal design of judicial systems.